Self and other body perception in anorexia nervosa: The role of posterior DMN nodes. (3rd April 2018) - Via, Esther; Goldberg, Ximena; Sánchez, Isabel; Forcano, Laura; Harrison, Ben J.; Davey, Christopher G.; Pujol, Jesús; Martínez-Zalacaín, Ignacio; Fernández-Aranda, Fernando; Soriano-Mas, Carles; Cardoner, Narcís; Menchón, José M.
Abstract: Objectives: Body image distortion is a core symptom of anorexia nervosa (AN), which involves alterations in self- (and other's) evaluative processes arising during body perception. At a neural level, self-related information is thought to rely on areas of the so-called default mode network (DMN), which, additionally, shows prominent synchronised activity at rest. Methods: Twenty female patients with AN and 20 matched healthy controls were scanned using magnetic resonance imaging when: (a) viewing video clips of their own body and another's body; (b) at rest. Between-group differences within the DMN during task performance were evaluated and further explored for task-related and resting-state-related functional connectivity alterations. Results: AN patients showed a hyperactivation of the dorsal posterior cingulate cortex during their own-body processing but a response failure to another's body processing at the precuneus and ventral PCC. Increased task-related connectivity was found between dPCC–dorsal anterior cingulate cortex and precuneus–mid-temporal cortex. Further, AN patients showed decreased resting-state connectivity between the dPCC and the angular gyrus. Conclusions: The PCC and the precuneus are suggested as key components of a network supporting self–other-evaluative processes implicated in body distortion, while the existence of DMN alterations at rest might reflect a sustained, task-independent breakdown within this network in AN.